Innovativeness in organic farming system: The case of the Marche region - Selene Righi; Elena Viganò (Economia Agro-Alimentare)
The importance of research and innovation is crucial for addressing the challenges posed by evolving climatic and environmental conditions, along with the urgent need to mitigate greenhouse gas emissions and to deal with unstable markets. To establish Sustainable Agri-Food Systems, in environmental, social, and economic terms, it is essential to ensure access to technologies that can reduce biological and market risks. The objective of this paper is to understand how different factors influence the innovativeness of organic farmers in the Marche region, in Italy, with a particular focus on the adoption of a digital tool, Decision Support System (DSS). The analysis, developed through the application of the SEM model to a sample of organic farmers, highlights the significant role of support services in facilitating the implementation of innovations. Therefore, it is important for policymakers, especially at the regional level, to define specific and coherent measures that incentivize the adoption of innovations.